Single cell RNA-seq reveals the landscape of tumor and infiltrating immune cells in nasopharyngeal carcinoma. (1st May 2020) - Zhao, Jin; Guo, Can; Xiong, Fang; Yu, Jianjun; Ge, Junshang; Wang, Hui; Liao, Qianjin; Zhou, Yujuan; Gong, Qian; Xiang, Bo; Zhou, Ming; Li, Xiaoling; et al.
Abstract: Nasopharyngeal carcinoma (NPC) is one of the most malignant tumors in Southern China and southeast Asia, which is characterized by a dense lymphocyte infiltration and a poor prognosis. The emergence of single-cell sequencing represents a powerful tool to resolve tumor heterogeneity and delineate the complex communication among the tumor cells with neighboring stromal and immune cells in the tumor microenvironment (TME). Here, we performed single cell RNA-seq and analyzed tumor cells together with the infiltrating immune cells from three NPC tumor tissues. In our study, the malignant cells display the intra- and inter-tumoral heterogeneity among the individual patients. Analysis of the immune cells reveal the heterogeneous composition of the distinct immune cells and the various functional states of T cells in NPC tumors. Additionally, coupled with the reconstruct of the T cell receptor (TCR) sequences from immune cells full-length single-cell sequence data, we identify the diverse T cell clonotypes and expansion distribution in individual tumors. Overall, we firstly reveal the landscape of tumor and infiltrating immune cells in nasopharyngeal cancer. These results provide deeper insights on the mechanisms of tumor clearance by immune cells in the surrounding microenvironment, which will be helpful in improving the targeted and immune therapies for NPC. Highlights: Constructed the transcriptome profiles of malignant cells and infiltrating immune cells in NPC at single cell level. Single cell RNA-seq revealed the intra- and inter-tumoral heterogeneity of NPC in 3 patients. Classified the subtypes and unveiled the distinctive functional states of immune cells in NPC tissues of individual patients. Assembled the T cell receptor (TCR) sequences in tumor-infiltrating T cells from full-length single-cell sequence data. Identified the diverse T cell clonotypes and expansion distribution in individual tumors by the TCR analysis